Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/plants9091100
|View full text |Cite
|
Sign up to set email alerts
|

The East Asian Winter Monsoon Acts as a Major Selective Factor in the Intraspecific Differentiation of Drought-Tolerant Nitraria tangutorum in Northwest China

Abstract: The influence of Quaternary climate fluctuation on the geographical structure and genetic diversity of species distributed in the regions of the Qinghai–Tibet Plateau (QTP) has been well established. However, the underlying role of the East Asian monsoon system (EAMS) in shaping the genetic structure of the population and the demography of plants located in the arid northwest of China has not been explored. In the present study, Nitraria tangutorum, a drought-tolerant desert shrub that is distributed in the EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…It is likely that the northwestward movement of the East Asian monsoon intensified the spread from the eastern to western genetic groups. The important role of East Asian monsoon system in shaping population genetic structure has also been demonstrated in other plants in this region ( Yin et al., 2015 , 2020 ; Zhang et al., 2017b ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It is likely that the northwestward movement of the East Asian monsoon intensified the spread from the eastern to western genetic groups. The important role of East Asian monsoon system in shaping population genetic structure has also been demonstrated in other plants in this region ( Yin et al., 2015 , 2020 ; Zhang et al., 2017b ).…”
Section: Discussionmentioning
confidence: 67%
“…The arid northwest region of China is one of the largest mid-latitude, temperate, continental interior dryland areas in the world. The disjunctive deserts of this region (i.e., the Taklamakan Desert, Badain Jaran Desert, and Tengger Desert) ( Yang and Scuderi, 2010 ), have attracted increasing interest from researchers (e.g., Meng et al., 2015 ; Yin et al., 2015 ; Zhang et al., 2017b ; Zeng et al., 2018 ; Li et al., 2019 ; Zhao et al., 2019 ; Yin et al., 2020 ). These studies have revealed that three factors have played a role in shaping the population genetic structure of plants occurring in this region: increased aridification, subsequent desert expansion, and changes in the East Asian monsoon system ( Yin et al., 2015 , 2020 ; Zhang et al., 2017b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the level of cpDNA genetic diversity in the natural C. korshinskii populations is relatively higher (Hd = 0.29 ~ 1.00 and π = 0.00012 ~ 0.00085) compared to a sister species C. microphylla, in which the highest population genetic diversity is Hd = 0.771 and π = 0.0005 (Xu et al 2017). This is also higher than the other two constructive desert shrubs, with Reaumuria soongarica showing Hd = 0 ~ 0.600 and π = 0 ~ 0.00248 (Li et al 2012;Yin et al 2015) and Nitraria tangutorum showing Hd = 0.928 and π = 0.0007 (Yin et al 2020). In addition, the genetic diversity level of the afforested C. korshinskii populations in this study is also similar to or even higher (Hd = 0.64 ~ 1.00 and π = 0.00033 ~ 0.00073) than that of wild desert shrubs.…”
Section: Potential Degradation Risk Of the Natural C Korshinskii Populationsmentioning
confidence: 88%
“…Deserts in marginal monsoonal zones tend to experience frequent contractions and expansions during glacial and interglacial periods (Lu et al, 2013), during which times the dynamics (such as the distribution ranges and effective population size) of desert plants in this region are significantly sped up (Yin et al, 2015;Qian et al, 2016), which sheds an interesting light on the influence of climate change on the demographic history of desert plant species (Wang et al, 2013;Ignace et al, 2018;Shi et al, 2020;Yin et al, 2020). During long-term adaptation to monsoonal climate change and heterogeneous environments, those populations can be expected to harbor more valuable genetic resources.…”
Section: Introductionmentioning
confidence: 99%